284 Improving Adherence to Irish Hip Fracture Database Standards 1 and 2. (16th September 2019) - Hearne, Siofra; Smyth, Hannah; Monahan, Pheadra; McGowan, Hugh; Timmins, Shirley; Hillary, Paddy; Mahapatra, Anant; Walsh, Alan; Conlon, Ciaran; Dunnill, Eithne; Campbell, Eleanor; Carolann, Danielle; et al.
Abstract: Background: The Irish Hip Fracture Database (IHFD) National Report 2017 demonstrated poor performance across all six IHFD standards in our hospital. For the purpose of this study we focused on standards 1 and 2. IHFD standard 1: All patients with hip fracture should be admitted to an acute orthopaedic ward within 4 hours of ED presentation/ brought directly to theatre from ED within 4 hours, and IHFD standard 2: All patients with hip fracture who are medically fit should have surgery within 48 hours of admission and during normal working hours. Methods: We examined IHFD standards 1 and 2 from August 2017-January 2018 and August 2018-January 2019 after the appointment of an orthogeriatrician and use of the first Hip Fracture Pathway in August 2018. We also analysed data collected from February-April 2019 after amendment of the hip fracture pathway for patients presenting to the ED. Results: IHFD Standard 1: From August to January 2017, 2.5% of patients were admitted to an orthopaedic ward within 4 hours versus 18.1% in 2018. IHFD Standard 2: in 2017, 64.8% underwent surgery within 48 hours during working hours, versus 65.3% in 2018. From February to April 2019, 32.1% of patients were admitted to an orthopaedic ward within 4 hours (IFHD 1) and 56.6% of patients underwent surgery within 48 hours and during working hours (IFHD 2). Conclusion: Close collaboration between Emergency Medicine, Orthopaedic Surgery, Radiology, Nursing colleagues, Allied Health Professionals and Orthogeriatrics and amendment of the Hip Fracture Pathway have led to improvements in Standards 1 and 2. The addition of an orthogeriatric service in the hospital has resulted in an improvement in adherence to all IFHD standards. However, there are ongoing challenges to achieving Standard 2 including limited theatre access and increasing numbers of older patients on novel oral anticoagulants.